2019
DOI: 10.19070/2326-3350-1900073
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Acceptability and Palatability of Catfish (Clarias gariepinus ) Preserved with Scent Leaf (Ocimum gratissimum) and Bitter Leaf (Vernonia amygdalina ) Extracts

Abstract: The acceptability of catfish, Clarias gariepinus preserved with ethanolic extracts of scent leaf (Ocimum gratissimum) and bitter leaf (Vernonia amygdalina). The plants were divided into two portions, one portion was washed and the other unwashed before their extracts were made. The fish was prepared into smoked fish and pepper soup samples and a trained panel of judges was used to assess the acceptability make comments through a questionnaire. The results showed that the fish products preserved with unwashed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The importance given to bitterleaf soup in the eastern part of Nigeria might explain this. Studies have reported favourable acceptability status of bitterleaf soup [15] and fish preserved with bitterleaf [16].…”
Section: Sensory Evaluation Of Egusi Soupmentioning
confidence: 99%
“…The importance given to bitterleaf soup in the eastern part of Nigeria might explain this. Studies have reported favourable acceptability status of bitterleaf soup [15] and fish preserved with bitterleaf [16].…”
Section: Sensory Evaluation Of Egusi Soupmentioning
confidence: 99%